Ross Sea paleo-ice sheet drainage and deglacial history during and since the LGM - Anderson, John B.; Conway, Howard; Bart, Philip J.; Witus, Alexandra E.; Greenwood, Sarah L.; McKay, Robert M.; Hall, Brenda L.; Ackert, Robert P.; Licht, Kathy; Jakobsson, Martin; Stone, John O. (Quaternary Science Reviews, 2014)
Onshore and offshore studies show that an expanded, grounded ice sheet occupied the Ross Sea Embayment during the Last Glacial Maximum (LGM). Results from studies of till provenance and the orientation of geomorphic features on the continental shelf show that more than half of the grounded ice sheet consisted of East Antarctic ice flowing through Transantarctic Mountain (TAM) outlet glaciers; the remainder came from West Antarctica. Terrestrial data indicate little or no thickening in the upper catchment regions in both West and East Antarctica during the LGM. In contrast, evidence from the mouths of the southern and central TAM outlet glaciers indicate surface elevations between 1000 m and 1100 m (above present-day sea level). Farther north along the western margin of the Ross Ice Sheet, surface elevations reached 720 m on Ross Island, and 400 m at Terra Nova Bay. Evidence from Marie Byrd Land at the eastern margin of the ice sheet indicates that the elevation near the present-day grounding line was more than 800 m asl, while at Siple Dome in the central Ross Embayment, the surface elevation was about 950 m asl. Farther north, evidence that the ice sheet was grounded on the middle and the outer continental shelf during the LGM implies that surface elevations had to be at least 100 m above the LGM sea level. The apparent low surface profile and implied low basal shear stress in the central and eastern embayment suggests that although the ice streams may have slowed during the LGM, they remained active. Ice-sheet retreat from the western Ross Embayment during the Holocene is constrained by marine and terrestrial data. Ages from marine sediments suggest that the grounding line had retreated from its LGM outer shelf location only a few tens of kilometer to a location south of Coulman Island by ∼13 ka BP. The ice sheet margin was located in the vicinity of the Drygalski Ice Tongue by ∼11 ka BP, just north of Ross Island by ∼7.8 ka BP, and near Hatherton Glacier by ∼6.8 ka BP. Farther south, 10Be exposure ages from ...